Needs Analysis of Digital Evaluation Tool: Using Quizwhizzer for Arabic Tarkib Assessment Among Eighth Grade Students MTsN 1 Padang - Mutia Lutfi; Asrina Asrina; Hanomi Hanomi (Abjadia : International Journal of Education, 2026)
This study aims to analyze the need for QuizWhizzer as an evaluation tool in the Arabic language tarkib test for eighth-grade students at Madrasah Tsanawiyah Negeri 1 Padang City. This study used a mixed methods approach, combining qualitative and quantitative approaches to obtain a more comprehensive picture of the need for such an evaluation tool. Data collection techniques included observation, interviews, and expert validation of questionnaires. The study subjects consisted of 29 eighth-grade VIII.1 students and one Arabic language teacher. Data were collected over a two-week period through validated questionnaires and semi-structured interviews. The results showed that the learning evaluations currently conducted by teachers still use conventional methods, using paper and pen, which are time-consuming. Meanwhile, students expressed a desire to be able to see the evaluation results directly. Based on the questionnaire data, the need for analysis from teachers reached 85%, while from students it was 80%. These findings indicate that both teachers and students have a high need for the implementation of digital-based evaluation tools, particularly the use of QuizWhizzer in the Arabic language tarkib test.